PolaPerkembanganBiji dan Perubahan Mutu Benih Berbagai Kultivar Sorgum(Shorgum bicolor L.)”. - Agus Sanoto; Aslim Rasyad; Elza Zuhry (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objective of this research was to determine seeds development pattern and seed quality changesduring the development of some cultivars of sorghum. The researched was carried out at Faculty of Agricultural experiment station, University of Riau in Pekanbaru. The field experiment was arranged in a randomized block design, consisting of four sorghum cultivars in three replications. The cultivars were K1=GalurPatir 9, K2 =GalurPatir 10, K3 =VarietasPahat K4 =Varietas Mandau. Parameters observed were seed fresh weight, seed dry weight, water concentration, dry matteraccumulation rate, effective filling period, seed yield m-2, seed weight, first count test, standard germination test, and vigor test. Seed were harvestedevery five day beginning from 5 days after antheses (DAP) to 35 (DAP). Data were analyzed by using analysis of variance at significant level of 5%. The results showed that the pattern of seeddevelopment of all cultivars increased slowly from 5 to 10 DAP, then increased very rapidly from 10 to 20 DAP, and reached the maximum value at 25 DAP.Following that time the dry tent to decrease until 35 DAP. While the water concentration decreased very rapidly from 5 to 25 and decreased from 25 DAP to 35 (DAP). Dry matter accumulation rate (KPBK) of all cultivars ranged from 1.15 to 1.22 (mg/seed/day), and effective filling period was about 22 days. Seed quality at harvest was very high for allcultivars but, Patir 9 showed lower seed vigor compared toPahat, Mandau and Patir 10. Grain yield per m2was relatively equal among all cultivar with yield potential off around 3.18 to 4.9 tones per hectare. Key word : seed fresh weight, dryweight,cultivars, seed quality, sorghum